PENGARUH EKSTRAK ETANOL BAWANG PUTIH (Allium Sativum, Linn) TERHADAP PENURUNAN KADAR KOLESTROL PADA MENCIT (Mus Musculus) - Isfanda Isfanda; Andri Andri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Background: Lipids or fats can come from within and outside the body, about 80% of the lipids derived from within the rest are from outside the body. The process of lipid excretion per day 1 gram through the feces, too much food intake can cause high cholesterol levels in the blood, the disease most often affects people who are hypercholesterolemia is atherosclerosis, coronary heart disease (CHD). Use of cholesterol-lowering drugs too often can also cause myopathy, gastrointestinal disorders and rashes, therefore researchers want to examine the effect of garlic on cholesterol reduction in mice. Objective: To examine the effect of garlic extract on the decrease of total cholesterol of mice. Method: true experimental with pre and post control group test design. Result: statistic test in the form of Paired T Test and ANOVA test result shows that there is difference between treatment before and after giving garlic extract with significant value 0,00 0,05 and also there is difference between each treatment group with dose 0,5 has a 23% drop rate and 96% effectiveness in lowering cholesterol. Conclusion: This research showed that garlic ethanol extract with 0,5 ml concentration had good effectivity value to decrease mice cholesterol level.Keywords: atherosclerosis, congestif heart disease, garlic extract, hypercholesterolmeia, myopathy